Revealing the philosophy of Palang Pintu in Betawi’s wedding ceremony - Lambok Hermanto Sihombing (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2023)
Nowadays, wedding ceremonies in Indonesia are typically held in a manner distinct from the past. However, modern and traditional elements can be combined to ensure that the essence of preserving Indonesian tradition is always present in wedding ceremonies. Palang Pintu is one of the Betawi cultural traditions, which is typically performed during a wedding ceremony. This study aims to reveal the symbolic meanings and functions of Palang Pintu philosophy. The author utilized a qualitative approach to investigate the wedding traditions of Betawi. The dataset was compiled from academic articles and proceedings. In this study, the author applied Rolland Barthes' Semiotic approach to determine each symbol's connotative and denotative significance in the Palang Pintu tradition. Aside from it, the author also utilized Stuart Hall's Cultural Identity theory to examine how these symbols are viewed as the identity of Betawi. The findings indicate that Palang Pintu has religious, cultural, traditional, and aesthetic values. Those values symbolize the Betawi people's identity that must be preserved.   Prosesi pernikahan di Indonesia saat ini biasanya diadakan dengan cara yang berbeda dari masa lalu. Namun, pada dasarnya, unsur modern dan tradisional dapat dipadukan untuk memastikan esensi tradisi Indonesia selalu hadir dalam acara pernikahan di Indonesia. Palang Pintu merupakan salah satu contoh tradisi budaya Betawi yang biasanya dilakukan pada saat upacara pernikahan. Kajian ini bertujuan mengungkap makna simbolik dan fungsi filosofi Palang Pintu. Penulis menggunakan pendekatan kualitatif untuk menganalisis tradisi pernikahan orang Betawi. Data dalam penulisan ini diperoleh melalui sumber artikel akademik dan prosiding. Dalam penelitian ini, penulis menerapkan pendekatan Semiotik Rolland Barthes untuk menentukan makna konotatif dan denotatif setiap simbol dalam tradisi Palang Pintu. Selain itu, penulis juga menggunakan teori Identitas Budaya Stuart Hall untuk mengkaji bagaimana simbol-simbol tersebut dilihat sebagai identitas Betawi. Hasil kajian ini menunjukkan bahwa Palang Pintu memiliki nilai religi, budaya, tradisi, dan estetika. Nilai-nilai tersebut melambangkan identitas masyarakat Betawi yang harus dilestarikan.